The environmental health citizen interview tool: towards an inclusive qualitative environmental wellbeing approach in support of planetary health - Delbaere, Ben; Pereira Barboza, Evelise; Plüschke-Altof, Bianka; Chebotareva, Mariia; Van Rafelghem, Evelien; Blockmans, Lauren; Keune, Hans (Frontiers in Public Health, 2024)
BackgroundNature-based Solutions (NbS) are vital for addressing climate change and biodiversity loss, yet their benefits are often unequally distributed. This study introduces the Environmental Health Citizen Interview Tool, aiming to inclusively capture diverse perspectives on environmental wellbeing using qualitative research methods. The principles of epistemic justice and planetary health are central to its development.MethodsThe Environmental Health Citizen Interview Tool was developed as a qualitative tool, incorporating a simple visualization scoring system for responses. Six environmental health determinants were selected, with in-depth open-ended follow-up questions. Content validation involved transdisciplinary expert consultation. A guidebook for using the tool was also developed.FindingsThe tool offers a comprehensive approach to inquire environmental wellbeing, accommodating diverse perspectives through in-depth inquiries. Limitations include the need for further validation and testing.InterpretationThe Environmental Health Citizen Interview Tool provides a practical framework for inclusive assessment of environmental wellbeing, aligned with planetary health and epistemic justice principles. Its application should be complemented by quantitative environmental monitoring such as air quality and be contextualized by local researchers for reliability and relevance. Future research should focus on refining the tool and exploring its utility in diverse settings to inform equitable local policy interventions.